2019
DOI: 10.3897/herpetozoa.32.e35663
|View full text |Cite
|
Sign up to set email alerts
|

A case of communal egg-laying of Gonatodes albogularis (Sauria, Sphaerodactylidae) in bromeliads (Poales, Bromeliaceae)

Abstract: The Neotropical Yellow-Headed Gecko Gonatodesalbogularis commonly use cavities in the trees as a microhabitat for egg-laying. Here, we present the first record of this species in Colombia using the tank bromeliad Tillandsiaelongata as nesting sites, along with the occurrence of communal egg-laying in that microhabitat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This does not mean, however, that TreMs are absent from these areas or have no ecological value. As part of our literature review, we identified studies of species dependent on individual TreMs conducted in the tropical forest (Whitfield et al, 2005;Cockle et al, 2012;Carvajal-Ocampo et al, 2019) and in the savanna (Pringle et al, 2015;Haddad, 2016). It is also likely that new TreMs absent from the Larrieu et al (2018a) typology can be observed in these areas, such as bromeliads (Rogy et al, 2019).…”
Section: Is the Trem Concept Applicable In Tropicalmentioning
confidence: 99%
“…This does not mean, however, that TreMs are absent from these areas or have no ecological value. As part of our literature review, we identified studies of species dependent on individual TreMs conducted in the tropical forest (Whitfield et al, 2005;Cockle et al, 2012;Carvajal-Ocampo et al, 2019) and in the savanna (Pringle et al, 2015;Haddad, 2016). It is also likely that new TreMs absent from the Larrieu et al (2018a) typology can be observed in these areas, such as bromeliads (Rogy et al, 2019).…”
Section: Is the Trem Concept Applicable In Tropicalmentioning
confidence: 99%
“…Recorded observations of communal nesting in lizards of different families have increased in neotropical regions, including Teiidae (Magnusson andLima 1984, Filadelfo et al 2013), Dactyloidae (Montgomery et al 2011), Sphaerodactylidae (Oda 2004, Oliveira et al 2014, Carvajal-Ocampo et al 2019, Sales et al 2020), Phyllodactylidae (Vitt 1986, Rigui et al 2004, Ávila and Cunha-Avellar 2005, Cassimiro and Rodrigues 2010, Lima et al 2011, Domingos et al 2017, and Gekkonidae Freire 2010, Bezerra et al 2011). Communal nests have been reported for the gekkonid genus Lygodactylus on the African continent (Greer 1967, Simbotwe 1983, Rodríguez-Prieto et al 2010), but currently no records of this behavior have been reported for South American species.…”
mentioning
confidence: 99%